Microbial Examination of Bacteria Isolated from Raw Beef Samples Sold in Opolo Market, Yenagoa Metropolis, Bayelsa State, Nigeria - I. Oku; T. W. Oyadougha; D. Y. Emmanuel (Journal of Applied Sciences and Environmental Management, 2023)
The objective of this paper is to evaluate the microbial examination of bacteria isolates in beef sold in Opolo market Yenagoa metropolis, Bayelsa State Nigeria using standard microbial techniques. The research was carried out for a period of four (4) months. Total viable counts of beef samples obtained from the marketanges from 7.3 X 102cfu/ml to 9.9 X 102cfu/ml for vendors a, b and cn nutrient agar and 6.4 X 102cfu/ml to 8.0 X 102cfu/ml on cetrimide agar for vendors A, B and C for the three vendors. Beef samples from Vendor B had the highest bacterial count 9.9 X 102cfu/ml on nutrient agar while the sample from Vendor C had the highest bacterial count 8.0 X 102cfu/ml on cetrimide agar. The Bacteria encountered in the beef samples were Staphylococcus aureus, Micrococcus luteus, Pseudomonas aeruginosa, Salmonella typhimurium and Bacillus cereus. The percentage of occurrence of bacteria isolates present in beef samples from Opolo Market showed Micrococcus luteusas the highest occurring bacteria isolate with 55% occurrence and Salmonella typhimuriumas lowest occurring bacteria isolate with 5% occurrence.